A Brief Review of Phasor Measurement Units as Sensors for Smart Grid. Issue 4 (25th February 2016) - Mohanta, Dusmanta Kumar; Murthy, Cherukuri; Sinha Roy, Diptendu
Abstract: Basic phasor measurement units are the sensing devices that capture power system phasors synchronously over wide geographical areas with high precision by means of global positioning system enabled time-stamping. The data obtained from phasor measurement units form the basis of all monitoring and control actions for wide-area measurement systems, and hence, phasor measurement units are the edifice of a wide-area measurement system. Within the purview of phasor measurement units, there have been diverse research contributions made in past decades. This article presents a brief review of phasor measurement units performing their functions as smart sensors. The review includes their evolution, optimal placement, applications, and reliability assessment. The main contributions pertain to segregation of research findings into broad domains with corroborations to validate phasor measurement units as the efficient sensors for the smart grid.